Daughters of the budding yeast from old mothers have shorter replicative lifespans but not total lifespans. Are DNA damage and rDNA instability the factors that determine longevity?. Issue 10 (19th May 2018) - Molon, Mateusz; Panek, Anita; Molestak, Eliza; Skoneczny, Marek; Tchorzewski, Marek; Wnuk, Maciej
ABSTRACT: Although a lot of effort has been put into the search for factors responsible for aging in yeast mother cells, our knowledge of cellular changes in daughter cells originating from old mothers is still very limited. It has been shown that an old mother is not able to compensate for all negative changes within its cell and therefore transfers them to the bud. In this paper, we show for the first time that daughter cells of an old mother have a reset lifespan expressed in units of time despite drastic reduction of their budding lifespan, which suggests that a single yeast cell has a fixed programmed longevity regardless of the time point at which it was originated. Moreover, in our study we found that longevity parameters are not correlated with the rDNA level, DNA damage, chromosome structure or aging parameters (budding lifespan and total lifespan).